Endotoxin induces fibrosis in vascular endothelial cells through a mechanism dependent on transient receptor protein melastatin 7 activity. - Cesar Echeverría; Ignacio Montorfano; Tamara Hermosilla; Ricardo Armisén; Luis A Velásquez; Claudio Cabello-Verrugio; Diego Varela; Felipe Simon (PLoS ONE, 2014)
The pathogenesis of systemic inflammatory diseases, including endotoxemia-derived sepsis syndrome, is characterized by endothelial dysfunction. It has been demonstrated that the endotoxin lipopolysaccharide (LPS) induces the conversion of endothelial cells (ECs) into activated fibroblasts through endothelial-to-mesenchymal transition mechanism. Fibrogenesis is highly dependent on intracellular Ca2+ concentration increases through the participation of calcium channels. However, the specific molecular identity of the calcium channel that mediates the Ca2+ influx during endotoxin-induced endothelial fibrosis is still unknown. Transient receptor potential melastatin 7 (TRPM7) is a calcium channel that is expressed in many cell types, including ECs. TRPM7 is involved in a number of crucial processes such as the conversion of fibroblasts into activated fibroblasts, or myofibroblasts, being responsible for the development of several characteristics of them. However, the role of the TRPM7 ion channel in endotoxin-induced endothelial fibrosis is unknown. Thus, our aim was to study whether the TRPM7 calcium channel participates in endotoxin-induced endothelial fibrosis. Using primary cultures of ECs, we demonstrated that TRPM7 is a crucial protein involved in endotoxin-induced endothelial fibrosis. Suppression of TRPM7 expression protected ECs from the fibrogenic process stimulated by endotoxin. Downregulation of TRPM7 prevented the endotoxin-induced endothelial markers decrease and fibrotic genes increase in ECs. In addition, TRPM7 downregulation abolished the endotoxin-induced increase in ECM proteins in ECs. Furthermore, we showed that intracellular Ca2+ levels were greatly increased upon LPS challenge in a mechanism dependent on TRPM7 expression. These results demonstrate that TRPM7 is a key protein involved in the mechanism underlying endotoxin-induced endothelial fibrosis.